Recycling strategy as a consequence of socio economic growth. The case of an Italian Sme - Saita, Massimo; Franceschelli, Maria Vittoria (Piccola Impresa / Small Business, 2016)
This paper aims to highlight how socio-economic growth and environmental strategy become more and more interdependent. Following this purpose, the paper showcases a medium-size Italian company, operative in Europe and Latin America that develops an innovative “dry constructions system”: the GreenService which aims to find new applications for the leftover gypsum. Today the percentage of recycled gypsum amount to 28%. Such an achievement is representative of the unique position this Italian company holds. According to the green economy model, a company’s decision process must look beyond the benefits procured by its own operation: strategies are being implemented due to the new market values that are dominating the scene. The implementation of an environmental strategy needs substantial investments and, most of the time confers an advantage, in the long-term. Alfa does not show economic advantages, even if it has implemented one of the best environmental practices in the recycling field.